Ethnicity, culture, and communication - Parvin, Sitara (Dhaka : University of Dhaka, 1997)
Examines the communication environment of the Bangladeshi community in Bradford, a northern British city; based on research done during 1986-1988.
Includes bibliographical references (p. [314]-326).
Keywords: Bangladeshis -- England -- Bradford (Unitary authority); Bangladeshis -- England -- Bradford (Unitary authority) -- Social conditions; Bradford (England : Unitary authority) -- Ethnic relations; Bangladesh -- Emigration and immigration